Understanding, Acceptance, and Perception of the Vision, Mission, Goals, and Objectives of the Northwestern University College of Business Education Stakeholders - Eric S Parilla; Marc Edward Abadilla; Glory Domingo; Jayson Tan (Research Synergy Foundation, 2023)
This research focuses on how various parties view and comprehend Northwestern University's Vision, Mission, Goals, and Objectives (VMGO) and whether they are aligned with them. Specifically, the study examines the stakeholders' awareness, acceptance, understanding, congruence, clarity, and perception. Stakeholders consisted of the students, faculty and staff, alumni, and industry partners. The research used structural equation modeling to find the links between awareness, acceptance, and understanding, congruency and clarity and perception. The study's findings were that the three variables relate to each other; however, the personal profile of the respondents only affected the awareness, acceptance, and understanding variables. This indicates that, for example, the age of the stakeholder, the older the stakeholder, the more he is aware of and comprehends the VMGO of the University. Moreover, this study recommends that the Institution continues to think of ways how to let its stakeholders comprehend the VMGO of the University.